Graft preservation in heart transplantation: current approaches - Lechiancole, Andrea; Sponga, Sandro; Benedetti, Giovanni; Semeraro, Arianna; Guzzi, Giorgio; Daffarra, Cristian; Meneguzzi, Matteo; Nalli, Chiara; Piani, Daniela; Bressan, Marilyn; Livi, Ugolino; Vendramin, Igor (Frontiers in Cardiovascular Medicine, 2023)
Heart transplantation (HTx) represents the current best surgical treatment for patients affected by end-stage heart failure. However, with the improvement of medical and interventional therapies, the population of HTx candidates is increasingly old and at high-risk for mortality and complications. Moreover, the use of “extended donor criteria” to deal with the shortage of donors could increase the risk of worse outcomes after HTx. In this setting, the strategy of donor organ preservation could significantly affect HTx results. The most widely used technique for donor organ preservation is static cold storage in ice. New techniques that are clinically being used for donor heart preservation include static controlled hypothermia and machine perfusion (MP) systems. Controlled hypothermia allows for a monitored cold storage between 4°C and 8°C. This simple technique seems to better preserve the donor heart when compared to ice, probably avoiding tissue injury due to sub-zero °C temperatures. MP platforms are divided in normothermic and hypothermic, and continuously perfuse the donor heart, reducing ischemic time, a well-known independent risk factor for mortality after HTx. Also, normothermic MP permits to evaluate marginal donor grafts, and could represent a safe and effective technique to expand the available donor pool. However, despite the increasing number of donor hearts preserved with these new approaches, whether these techniques could be considered superior to traditional CS still represents a matter of debate. The aim of this review is to summarize and critically assess the available clinical data on donor heart preservation strategies employed for HTx.